ANALISIS KUALITAS APLIKASI UJIAN ONLINE BERBASIS WEB PADA PERUM PERUMNAS - Hoga Saragih; Siti Safarina (Faculty of Computer Science Universitas Indonesia, 2014)
Human Resources Department utilizing information and communication technology development to further improve the quality of the company's employees. One of them by developing a Web-Based Employee Application Exam. Department of Human Resources at Housing realize that the role of employees determine the success or failure of the company to achieve its objectives. With a good selection implementation process, employees received will be qualified so that coaching, development, and setting employees becomes easier. This research will evaluate the quality of a website online exam based on the Web-site Quality Evaluation Method. The results of the analysis indicate that website quality is not satisfactory, so the need for design development of a prototype website using the Spiral Development Method.